Analysis of International Competition and Training in Men's Field Hockey by Global Positioning System and Inertial Sensor Technology. Issue 1 (January 2015) - White, Andrew D.; MacFarlane, Niall G.
Abstract : Abstract: White, AD and MacFarlane, NG. Analysis of international competition and training in men's field hockey by global positioning system and inertial sensor technology. J Strength Cond Res 29(1): 137–143, 2015—This study assessed the relative demands of elite field hockey training and competition to determine whether familiar exercise prescription strategies provide an appropriate training stimulus. Sixteen elite male field hockey players (age, 25 ± 4 years; body mass, 70.9 ± 6.6 kg; and maximal oxygen consumption, 61.0 ± 2.1 ml·kg −1 ·min −1 [mean ± SD ]) participated in the study. Seventy-five elite level competition and 37 training analyses from 8 games and 4 training sessions were obtained. Training duration was longer than competition and covered a greater total distance (109 ± 2.5 vs. 74 ± 0.3 minutes and 7318 ± 221 vs. 5868 ± 75 m; p < 0.001 in both). The distance covered sprinting and running at high intensity was not different between training and competition (114 ± 6 vs. 116 ± 9 m when sprinting and 457 ± 6 vs. 448 ± 7 m for high-intensity running). More high-intensity accelerations were performed during training than in competition (37 ± 3 vs. 20 ± 2). Despite having lower predicted aerobic capacity and covering less distance in competition than in some previous studies, these data support the suggestion that it is high-intensity activity that differentiates international level competition and further suggests that international players can replicate the intensity of competition during small-sided games.